The Effect of Project-Based Learning Models on Science Learning Outcomes of Fifth Grade Students - Simatupang, Jonathan; Sihombing, Lisbet Novianti; Lumbantobing, Minar T. (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the Effect of Project Based Learning Model on Science Learning Outcomes of Fifth Grade Students of UPTD Sd Negeri 124385. The research design implemented is the Pre-Experimental Designs method. In this study, the population is all fifth grade students of UPTD SD Negeri 124385 Pematangsiantar. In this study, researchers chose to use a sampling technique with Total Sampling Based on the results of the research and discussion, it can be concluded that the results of the research study that have been selected with predetermined criteria that based on the results of the study there is an influence of the project based learning model on student learning outcomes obtained a pretest value of 48.40 and a posttest value of 83.20 which means there is an influence of the project based learning model on Learning 1-2 Theme 3 Subtheme 1 How the Body Processes Food in Fifth Grade UPTD SD Negeri 124385 Pematangsiantar. It can be concluded that by using the Project Based Learning model, it is effective to improve student learning outcomes. This explanation shows that Ha is accepted and H0 is rejected, meaning that there is an influence of the Project Based Learning Model on student learning outcomes in sub-theme 1 of learning 1 and 2 in class V of UPTD SD Negeri 124385 Pematangsiantar in the 2024/2025 academic year